Optimization of ostrich eggshell catalyst in transesterification using waste cooking oil via response surface methodology - Tan, Yie Hua Yie; Abdullah, Mohammad Omar; Kansedo, Jibrail; Saptoro, Agus; Nolasco Hipolito, Cirilo (UNIMAS Publisher, 2018)
In this research work, waste cooking oil biodiesel production was optimized using a design of experiment (DOE) approach: response surface methodology (RSM), based on a five level, three variables central composite design (CCD) to investigate the interaction effects of the different combination of transesterification reaction variables such as catalyst concentration, reaction temperature and time, using ostrich eggshell CaO base catalyst. A quadratic polynomial equation of the response, biodiesel yield was attained via multiple regression analysis to predict the relation between yield and the chosen variables. The results showed that the temperature and time are the most important process parameters on the biodiesel production. The optimal operating conditions for the transesterification reaction have been found to be: reaction temperature of 67 °C, alcohol/oil molar ratio of 10:1 (fixed parameter), catalyst concentration of 1.97 % w/w and reaction time of 1.77 h. The predicted biodiesel yield was about 99.67% under the optimal conditions through the ANOVA numerical method.
Keywords: Producción de biodiésel; Catalizador heterogéneo; Cáscara de huevo de avestruz; Metodología de superficie de respuesta